The Effect of Motivation and Job Stress towards Employee Performance in PT. ABC - Stefannie Stefannie; Priscilla Audrey Bianca (iBuss Management, 2022)
Motivation is the process that initiates, guides, and maintains goal-oriented behavior and is related to the performance of an individual in the workplace while Job stress is a phenomenon that affects employees differently, in different work contexts that could create an imbalance in a company. Both motivation and job stress could affect employee performance, especially in PT. ABC (not the real name). The researchers are using simple random sampling as a sample design by distributing a questionnaire through social media and analyzing it with BLUE classical assumption, and multiple linear regression by using SPSS. From 100 respondents, the result shows that motivation and job stress have a significant relationship with employee performance shown by the F-test and t-test. It also shows that motivation affects employee performance positively while job stress affects employee performance negatively. In conclusion, the result of the research shows that motivation could lead to better employee performance. This should be supported by keeping the motivation of the employees. It is also important to pay attention to the job stress which might occur in the company as it could lead to decreasing employee performance.Keywords: Motivation, Job stress, Employee performance, Human resource, Quantitative analysis